CFD simulation of air temperature inside a bus passenger compartment - Ahmad Shafie, Noor Emilia (2015)
Good ventilation is important for passenger for sufficient supply of fresh air during commuting in a bus. Insufficient fresh air causes feeling of uncomfortable to passenger and affects passenger’s health. Airborne transmission disease, headache and respiratory allergies are the usual health symptoms. This paper presents the CFD study of air flow inside a bus passenger compartment. The objective is to estimate the temperature level at the diffuser, seat and floor locations of the bus passenger compartment. Two conditions of airflow velocity at the supply diffuser were examined, namely 2.7 m/s and 3.1 m/s. A CFD Fluent software was employed to develop and meshed a simplified 3D model of a quarter section of a bus passenger compartment. Air velocity and temperature boundary conditions were prescribed on the model based on the actual data obtained from field measurement. Turbulent flow analyses were carried out using standard k-e model to visualize the air flow distribution inside the compartment. The results show that the velocity distribution is uniform when the diffuser air velocity is 3.1 m/s. When the diffuser air velocity is 3.1 m/s the air temperature of the seat area was decreased by 0.3°C. The air temperature inside the cabin can be maintained uniform at 23°C when diffuser air velocity was fixed at 3.1 m/s.